Development scale model of steam engine with Stephenson gearing system - Zulhelmi, Zainal (2007)
This Final Year Project is about development scale model of steam engine with Stephenson Gearing System. Steam engine is device that use steam power to produce mechanical energy for a variety application. In actual operations, steam engine operates with low efficiency because of the bad management of steam intake and steam exhaust at the engine cylinder. This major problem can be encounter by equipping the Stephenson Gearing System at the steam engine. The objectives of this project are to design the steam engine components base on Mechanical Principles of Steam Engine and to investigate the Stephenson Gearing System operation in order to increase steam engine efficiency. All of the designed components are analyze with the calculation analysis of steam engine and the effectiveness of Stephenson Gearing System is showing in the motion simulation of the steam engine. Then best manufacturing process to fabricate this steam engine is discussed and this will help during fabrication session. So, the scale model of steam engine is ready to fabricate if the analysis and simulation on scale model of steam engine produce the positive results.